Effects of Inorganic Salts on Curdlan Production and Structural Properties - Xinyi Zhu; Bowei Yao; Siyang Yue; Zhongyi Chang; Xuexia Yang; Hongliang Gao (Gels)
This research investigates the influence of inorganic salts on curdlan production, gel strength, molecular weight (Mw), and texture properties, to provide insights into optimizing fermentation conditions. Five different inorganic salts were individually incorporated into the fermentation medium to assess their impact. The results showed that FeCl3 significantly reduced curdlan yield, Mw, and gel quality, indicating its unsuitability for curdlan fermentation. FeSO4 at 0.01% enhanced yield, gel strength, and texture properties, such as springiness and chewiness, though higher concentrations had adverse effects. MnCl2 exhibited limited impact on yield, with low concentrations notably decreasing gel strength, hardness, springiness, and chewiness. CoCl2 was the most effective additive, with a concentration of 0.002% achieving optimal results for yield, Mw, gel strength, and texture, though higher levels diminished these benefits. ZnCl2 at 0.04% improved gel strength, chewiness, and Mw but had minimal effect on other properties. A correlation (R2 = 0.5064) was observed between Mw and gel strength, indicating Mw’s critical role in curdlan’s mechanical properties. Overall, CoCl2 and FeSO4 at specific concentrations demonstrated potential for enhancing curdlan quality and offered practical insights for tailoring fermentation processes to achieve desired properties in industrial applications.